(untitled) (Linguostylistic Studies, 2015)
The certain article is devoted to the problem of investigation the peculiarities of explication the category of evaluation in fiction discourse. In this article the role of the verbs of representation in realization the category of evaluation is analyzed. The verbs of representation are divided into three groups: a) the verbs which possess a distinctive seme « evaluation» (the verbs to like and to hate). b) the verbs which express an evaluation contextually. The verbs of this group can explicate themselves only in the certain context where they can express the positive or negative evaluation. c) the verbs of substitution (to do, to be). These verbs can be considered as the auxiliary and representative. In both of these functions they explicate the category of evaluation. The verbs of substitution in the negative form obtain the meaning of evaluation, i.e. can change this meaning from positive to negative and V.V. Key words: category of evaluation, explication, verbs of representation, verbs of substitution, link verbs, lexico-semantic field. References